2018
DOI: 10.1161/jaha.118.009835
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coenzyme Q10 on Statin‐Induced Myopathy: An Updated Meta‐Analysis of Randomized Controlled Trials

Abstract: Background Previous studies have demonstrated a possible association between the induction of coenzyme Q10 (CoQ10) after statin treatment and statin‐induced myopathy. However, whether CoQ10 supplementation ameliorates statin‐induced myopathy remains unclear. Methods and Results PubMed, EMBASE , and Cochrane Library were searched to identify randomized controlled trials investigating the effect of CoQ10 on statin‐induced myopathy. We calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
16

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(89 citation statements)
references
References 38 publications
2
71
0
16
Order By: Relevance
“…This result is supported by clinical trials showing that tested drug may improve statin induced myopathy. 38 The results of metformin treatment in DM+I/R group was in line with that of Q10. Metformin caused significantly more improvement in glycemic control, muscle parameter CKMM and IL6 and most of oxidative stress parameters.…”
Section: A B Csupporting
confidence: 75%
“…This result is supported by clinical trials showing that tested drug may improve statin induced myopathy. 38 The results of metformin treatment in DM+I/R group was in line with that of Q10. Metformin caused significantly more improvement in glycemic control, muscle parameter CKMM and IL6 and most of oxidative stress parameters.…”
Section: A B Csupporting
confidence: 75%
“…Furthermore, Abdel-Kader et al [2007] reported that EGb761 restored mitochondrial functions in an in vitro model of aging. Recently, a metaanalysis of RCTs showed that CoQ 10 supplementation alleviated statin-induced muscle symptoms [Qu et al, 2018a]. Altogether, it is likely that EGb761 elevated CoQ 10 levels, possibly through augmenting CoQ 10 biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…atorvastatin) used in the treatment of hypercholesterolemia in type 2 diabetes [68,69]. Hence, CoQ10 supplementation for statin induced muscle symptoms have opened a new avenue in the complementary management of statin-induced myopathy in type 2 diabetic patients [70].…”
Section: Role Of Ubiquinonementioning
confidence: 99%